Structural studies and magnetism of Dy6Ni2.43Sn0.5 stannide - Romaka, L.; Miliyanchuk, Kh.; Romaka, V.V.; Havela, L.; Stadnyk, Y. (Physics and Chemistry of Solid State, 2023)
Intermetallic compound Dy6Ni2.43Sn0.5 was prepared by arc melting and annealing at 873 K. It was characterized by X-ray powder diffraction, differential thermal analysis, and electron probe microanalysis. The crystal structure of low temperature Dy6Ni2.43Sn0.5 phase belongs to the orthorhombic Ho6Co2Ga structure type (space group Immm, a = 0.93116(1) nm, b = 0.94993(1) nm, c = 0.98947(1) nm). Crystal structure refinements showed the deviation from the ideal 6:2:1 stoichiometry corresponding to the formula Dy6Ni2.43Sn0.5. It exhibits a sequence of magnetic phase transitions; antiferromagnetic ordering sets in at 60 K, while further order-order magnetic phase transitions take place at lower temperatures.